TGF-β1 protection against Aβ1–42-induced hippocampal neuronal inflammation and apoptosis by TβR-I. Issue 2 (17th January 2018) - Fang, Xiao-Xia; Sun, Gao-Lin; Zhou, Yi; Qiu, Yi-Hua; Peng, Yu-Ping
Abstract : Alzheimer's disease (AD), the most common chronic neurodegenerative disease, is pathologically characterized by the formation of neurofibrillary tangles because of hyperphosphorylation of tau protein and extracellular deposits of amyloid-β (Aβ) protein termed senile plaques. Recent studies indicate that neuronal apoptosis caused by chronic neuroinflammation is one of the important pathogenesis of AD. Transforming growth factor (TGF)-β1 is a pleiotropic cytokine with immunosuppressive and anti-inflammatory properties. However, it is poorly known whether the anti-inflammatory property of TGF-β1 is involved in a neuroprotection in AD. Here, an AD cell model of hippocampal neurons induced by Aβ1–42 was used to show an anti-inflammatory and neuroprotective effect of TGF-β1 through its receptor transforming growth factor-β receptor type I (TβR-I). As expected, Aβ1–42 -induced an upregulation in neuronal expression of amyloid precursor protein (APP), tumor necrosis factor-α, cyclooxygenase-2, Bax, cleaved caspase-3, and cleaved caspase-9, and a downregulation in the expression of Bcl-2, as well as an increase in the number of NeuN/terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) double-positive cells. TGF-β1 pretreatment reduced the Aβ1–42 -induced effects of upregulating APP, tumor necrosis factor-α, Bax, cleaved caspase-3 and cleaved caspase-9, and downregulating Bcl-2, in addition to increasing NeuN + TUNEL + cell number. TβR-I expression in hippocampal neurons was downregulated by Aβ1–42 exposure, but upregulated by TGF-β1 pretreatment. Silencing of the TβR-I gene in the neurons abolished the anti-inflammatory and antiapoptotic effects of TGF-β1 in the Aβ1–42 -induced AD cell model. These findings suggest that TGF-β1 protects neurons against Aβ1–42 -induced neuronal inflammation and apoptosis by activation of TβR-I.